Use of Mobile Devices in Academic Libraries in Nigeria: are Students Distracted? - Nwafor-Orizu, Obianuju E.; Ezejiofor, Victoria O.; Ibe, Oluchi; Okonkwo, Ifeyinwa (Communicate: Journal of Library and Information Science, 2024)
The use of mobile devices has the potential for distraction in libraries is undeniable despite the excellent enhancement they have brought to learning and life in general. Librarians are still searching for evidence-based solutions to tame this emergent tide. The study is a feedback exercise to find out in specific terms whether the burden of noise generated by the use of mobile devices in libraries weighs down the students’ concentration to harvest their individual views on effective control measures. It is a descriptive survey study that used a structured questionnaire to elicit data from three hundred and forty (340) students of Chukwuemeka Odumegwu Ojukwu University, Nigeria. A simultaneous face-to-face approach was adopted in the classroom setting for data collection. SPSS was used to analyse the quantitative data. Findings reveal that 62.06% of the students feel disturbed and distracted by mobile phone use especially noise from answering of calls and ringing tones. As a solution, the majority of respondents (71%) recommend an outright ban on the use of mobile devices in the library. It is recommended that library management battling with noise control may consider a ban on mobile devices use in the library for possible relief.